2022
DOI: 10.3389/fcell.2022.848682
|View full text |Cite
|
Sign up to set email alerts
|

SHetA2 Attack on Mortalin and Colleagues in Cancer Therapy and Prevention

Abstract: Heat Shock Proteins of the 70-kDa family (HSP70s) do not cause cancer by themselves, but instead protect cells as they transform into cancer. These molecular chaperones bind numerous client proteins and utilize ATP hydrolysis to facilitate proper protein folding, formation of functional complexes and cellular localizations, or degradation of irreparably damaged proteins. Their transient upregulation by stressful situations avoids induction of programmed cell death. Continued upregulation of the mortalin, heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…SHetA2 induced caspase-dependent apoptosis in ovarian, kidney, and lung cancer cells ( 23 26 ). As expected and consistent with our previous SiHa xenograft study ( 6 ), SHetA2 significantly induced caspase-3 activity in cervical cancer cell lines ( Figure 6A ). Inhibition of caspase activity with a pan-caspase inhibitor, as confirmed by caspase-3 assay ( Figure 6A ), did not significantly alter SHetA2 cytotoxicity, suggesting that SHetA2 works independently of caspase activity in cervical cancer cell lines ( Figure 6B ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…SHetA2 induced caspase-dependent apoptosis in ovarian, kidney, and lung cancer cells ( 23 26 ). As expected and consistent with our previous SiHa xenograft study ( 6 ), SHetA2 significantly induced caspase-3 activity in cervical cancer cell lines ( Figure 6A ). Inhibition of caspase activity with a pan-caspase inhibitor, as confirmed by caspase-3 assay ( Figure 6A ), did not significantly alter SHetA2 cytotoxicity, suggesting that SHetA2 works independently of caspase activity in cervical cancer cell lines ( Figure 6B ).…”
Section: Resultssupporting
confidence: 92%
“…We next determined if these mitochondrial effects are also caused by SHetA2 treatment in an animal model. Previously, we demonstrated that oral administration of 60 mg/kg SHetA2 significantly inhibited the growth of SiHa cervical cancer xenografts without inducing toxicity ( 6 ). In this study, two oral doses (30 and 60 mg/kg/day) of SHetA2 induced a dose-responsive reduction in Ca Ski xenograft tumor growth ( Figure 9A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides its essential role in maintaining the mitochondrial integrity ( Czarnecka et al, 2006 ; Havalova et al, 2021 ), mortalin has been shown to interact with several proteins and modulate their functions in control of cell division and migration ( Wadhwa et al, 1998 ; Mizukoshi et al, 1999 ; Sacht et al, 1999 ; Takano et al, 2001 ; Schwarzer et al, 2002 ; Wadhwa et al, 2003 ; Chen et al, 2014 ). It has been demonstrated to interact with the key tumor suppressor protein p53, functionally inactivated in a large majority of cancers ( Wadhwa et al, 1998 ; Benbrook et al, 2014 ; Sane et al, 2014 ; Pham et al, 2019 ; Benbrook, 2022 ). The interaction of mortalin and p53 in the cytoplasm results in cytoplasmic retention and hence the inactivation of transcriptional activation function of p53 in cancer cells ( Wadhwa et al, 1998 ; Kaul et al, 2001 ; Wadhwa et al, 2002c ; Walker et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%